GUIDELINES FOR DRIVING PROFESSIONAL LEARNING COMMUNITY OF SCHOOLS UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE NONTHABURI - Punbo, Kanlayanee; Petchroj, Laddawan (Academic Journal Phranakhon Rajabhat University, 2021)
This research aimed to 1) study the school administrators and teachers’ opinions on the movement of professional learning communities (PLC), 2) compare the PLC movement, and 3) study the guidelines for driving PLC of schools under the Secondary Educational Service Area Office Nonthaburi. The samples were 334 administrators and teachers, selected by a stratified randomization method. The research instrument was a questionnaire with a consistency (IOC) of 0.89 and an alpha coefficient of 0.98. Data were analyzed by mean, standard deviation, t-test, one-way ANOVA, LSD and content analysis. The research findings revealed that the school administrators and teachers’ opinions on enhancing a professional learning community all of 6 elements were at a high level, arranged in descending order as shared vision ( =4.21, S.D.=.59), collaborative teamwork ( =4.18, S.D.=.66), professional learning and development ( =4.16, S.D.=.64), support structure ( =4.12, S.D.=.66), shared leadership, and caring community ( =4.12, S.D.=.70) respectively. When comparing the opinions classified by personal data, it was found that gender, educational level, year of service and position had no different opinion while difference in opinions was found in the aspect of age and school size with a statistically significant difference at .05 level. The 3 successions how to success in PLC were: allowing teachers to group by their interests, having the committees to drive PLC systematically, and setting the PLC period in the teaching schedule. The role of administrators is essential to drive PLCs in schools. They should support the implementation of the activities by educating and training teachers to understand clear methods, providing advice and monitoring regularly